Factors Affecting Medication Compliance of Patients with Schizophrenia at the Psychiatric Polyclinic of Dr. Mm Dunda Limboto Hospital - Indrawaty Djakatara; Fadli Syamsuddin; Nur Uyuun I. Biahimo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Schizophrenia is a serious mental disorder that affects the way a person thinks, feels, and acts. This disorder is characterized by psychotic symptoms such as hallucinations, delusions, thinking disorders, and social withdrawal. This study uses a cross sectional design. Cross-sectional is a design that aims to find an event in a phenomenon, situation, problem, behavior, or issue by taking a cross-section (representative example representing the whole) of a population. There was no long-term relationship between treatment and medication adherence for schizophrenia patients at the Psychiatric Polyclinic of MM Dunda Limboto Hospital with the results of the chi square statistical test showing a p-value = 0.061 (>0.05). There was a relationship between family knowledge and medication adherence for schizophrenia patients at the Psychiatric Polyclinic of MM Dunda Limboto Hospital with the results of the chi square statistical test showing a p-value = 0.011 (<0.05). There was a relationship between family support and medication adherence to schizophrenia patients at the Psychiatric Polyclinic of MM Dunda Limboto Hospital with the results of the chi square statistical test showing a p-value = 0.002 (<0.05).